Stressful Experiences, Connection, and Depressive Symptoms Among Taiwanese Han and Indigenous Youth - Yang, Pei-Jung (Frontiers in Psychology, 2021)
This study examined Taiwanese Han and indigenous (Tayal) youth’s experiences of stressful life events, the association between stressful experiences and depressive symptomology, as well as the indirect and interactive effects of connection on the relationship between stressful experiences and depressive symptomology. Taiwanese Han (97%) are the majority group, whereas indigenous people make up 2.3% of Taiwan’s population. Taiwanese indigenous people have experienced disparities across socio-historical, educational, and economic aspects of their lives. This study included 291 eighth-grade participants (40% from the Tayal tribe, 48.8% female, and Mage = 13.44). The Han sample in this study all lived in cities and the Tayal sample all lived in the tribal areas of the Northern Taiwan mountain regions. Person-centered (latent class analyses) and cumulative (sum of items) approaches were used to investigate family and school stressful events respectively. Hierarchical regression analyses were conducted separately for the Han and Tayal participants to examine the role of family and school connection in relation to family and school stressors and depressive symptomology. Our results showed that stressful experiences are clearly linked to depressive symptomology and family connection was important to both Tayal and Han youth in supporting their coping with depressive symptoms. However, Tayal youth might be particularly vulnerable to family stressful events because family stressors disrupted their connection with their parents, and thereby minimized the protective function of family relationships. To decrease the likely onset of depression during early adolescence, our results suggest that it is important for parents and other family members to monitor adolescents’ daily experiences of stress and provide support when needed. Furthermore, mental health interventions need to be tailored specifically for youth in specific racial, social and economic contexts. Tayal youth mental health might benefit particularly from increasing school connection and decreasing stresses experienced in family contexts. Implications, limitations and recommendations for future research are discussed.